Outcomes of mechanical support in a pediatric lung transplant center. Issue 3 (27th October 2016) - Toprak, Demet; Midyat, Levent; Freiberger, Dawn; Boyer, Debra; Fynn‐Thompson, Francis; Visner, Gary
Summary: Pediatric lung transplantation is a lifesaving option for patients with end stage lung disease, although the scarcity of suitable donor organs results in long wait times and increased waitlist mortality. Many pediatric centers consider mechanical ventilatory support, such as long‐term invasive ventilation and ECMO, a contraindication to lung transplantation. We hypothesized that current survival rates and outcomes for patients on mechanical ventilatory support in the pre‐transplant period were not remarkably different. In our retrospective analysis we included patients between the ages of 0–21 years listed for lung transplantation from deceased donors between 2007 and 2014 at our institution. One‐year survival outcomes were compared between three groups of patients: (i) patients bridged to transplant on ECMO (n = 6, 1‐year survival = 67%); (ii) patients needing mechanical ventilation (either through endotracheal intubation or tracheostomy) but not ECMO (n = 12, 1‐year survival = 75%); and (iii) patients who did not need endotracheal ventilation, tracheostomy, or ECMO (n = 25, 1‐year survival = 88%). Comparison of outcomes of transplanted patients between these three groups were not statistically different in terms of successful hospital discharge and 1‐year survival rates ( P > 0.05). We believe that "bridging" the end‐stage lung disease patient with long‐term mechanical ventilation and/or ECMO support is a reasonable option in selected patients until suitable donors become available.Pediatr Pulmonol. 2017;52:360–366. © 2016 Wiley Periodicals, Inc.